The roles of Facebook in student employment nowadays and policy recommendations - Lan Nguyen, Nguyen (VNU Journal of Science: Policy and Management Studies, 2020)
In recent times, with the rapid change of science and technology in the industrial revolution 4.0 as well as the very complex consequences of the Covid-19 pandemic, the issues on students’ employment (especially career guidance, job counseling and start-up support) are becoming increasingly urgent and attracting the attention of the whole society. To meet such practical requirements, since September 11, 2020, the Ministry of Education and Training has issued and started collecting comments on Draft circular regulating career guidance, job counsel ling and start-up support in educational institutions . This article focuses on analyzing some key roles of Facebook (the social network site used by many Vietnamese students) the current problems of Vietnamese students’ employment and drawing some relevant policy recommendations, thereby contributing positively to the completion of the above-mentioned draft circular.